Present-Day Greenland Ice Sheet Climate and Surface Mass Balance in CESM2 - van Kampenhout, Leonardus; Lenaerts, Jan T.M.; Lipscomb, William H.; Lhermitte, Stef; Noel, Brice; Vizcaino, Miren; Sacks, William J.; van den Broeke, Michiel R. (Journal of Geophysical Research: Earth Surface, 2020)
sponsorship: This work was carried out under the program of the Netherlands Earth System Science Centre (NESSC), financially supported by the Ministry of Education, Culture and Science (OCW, Grant 024.002.001). The CESM project is supported primarily by the National Science Foundation (NSF). This material is based upon work supported by the National Center for Atmospheric Research, which is a major facility sponsored by the NSF under Cooperative Agreement 1852977. Computing and data storage resources, including the Cheyenne supercomputer (doi:10.5065/D6RX99HX), were provided by the Computational and Information Systems Laboratory (CISL) at NCAR. We thank all the scientists, software engineers, and administrators who contributed to the development of CESM2. The HIST-EC climate simulation was performed on SURFsara HPC systems with support from NWO Exacte Wetenschappen. Climate data for simulations HIST-01 (historical.r1i1p1f1) to HIST-06 (historical.r6i1p1f1) are publicly available from Earth System Grid Federation (https://esgf.llnl.gov/nodes.html). Climate data for simulation HIST-EC are publicly available from Zenodo; native resolution https://doi.org/10.5281/zenodo.3369633, 11 km offline downscaled https://doi.org/10.5281/zenodo.3369635, and 1 km offline downscaled https://doi.org/10.5281/zenodo.3368630. RACMO climate data used in this paper are publicly available from Zenodo as well; 11 km native https://doi.org/10.5281/zenodo.3368404, and 1 km downscaled https://doi.org/10.5281/zenodo.3367210. (Ministry of Education, Culture and Science (OCW)|024.002.001, National Science Foundation (NSF), National Center for Atmospheric Research - NSF|1852977, NWO ExacteWetenschappen) status: Published